2005
DOI: 10.1002/mar.20079
|View full text |Cite
|
Sign up to set email alerts
|

For fun and profit: Hedonic value from image interactivity and responses toward an online store

Abstract: With the use of an on-line retailer's Web site and an experimental method with 103 university students, statistical support through path analysis was found for positive influences of optimum stimulation level (preferred level of environmental stimulation) and recreational shopping on hedonic value (trying an image-interactivity feature of an apparel Web site as a stimulating experience). The Web site's mix-andmatch image interactivity feature allowed creation of visual images of product combinations. The path-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
283
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 389 publications
(305 citation statements)
references
References 56 publications
14
283
1
7
Order By: Relevance
“…The results support past work (Fiore, Kim and Lee, 2005;Fiore and Kim, 2007;Song and Zinkhan, 2008) indicating that control plays a role in building user engagement. The findings also confirm prior studies by Shih (1998), Fiore, Jin and Kim (2005), Fiore, Kim and Lee (2005) and Steuer (1992) Algharabat and Dennis (2010b) supporting the role of 3D authenticity in user engagement. Through engagement, the telepresence components, along with utilitarian value (H1f) and hedonic value (H1g), indirectly positively influence the enjoyment a user derives from experiencing the simulated retail environment (H2).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results support past work (Fiore, Kim and Lee, 2005;Fiore and Kim, 2007;Song and Zinkhan, 2008) indicating that control plays a role in building user engagement. The findings also confirm prior studies by Shih (1998), Fiore, Jin and Kim (2005), Fiore, Kim and Lee (2005) and Steuer (1992) Algharabat and Dennis (2010b) supporting the role of 3D authenticity in user engagement. Through engagement, the telepresence components, along with utilitarian value (H1f) and hedonic value (H1g), indirectly positively influence the enjoyment a user derives from experiencing the simulated retail environment (H2).…”
Section: Discussionsupporting
confidence: 88%
“…However, more recent research suggests that shoppers also seek out recreational, enjoyable aspects of online shopping (Fiore, Jin and Kim, 2005;Konus et al, 2008). This study draws attention to the important differences between the two online environments, in that in the immersive environment, experience is more associated with engagement and enjoyment, leading to a greater purchase intention.…”
Section: Conclusion Managerial Implications and Future Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…Past research (e.g., Marmorstein et al, 1992) suggests that greater control of the shopping experience is associated with increased pleasure. Further, Fiore et al (2005) found that image interactivity was linked to increased pleasure. Therefore, increased levels of interactivity in a web-based shopping environment are also expected to have a positive relationship with pleasure.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Literature in e-commerce with image interactive technology showed that consumers' emotional pleasures and/or affect acquired in the online shopping environment influenced consumers' attitudes toward online shopping (e.g., Childers, Carr, Peck, & Carson, 2001;Fiore, Jin, & Kim, 2005;Kim, Fiore, & Lee, 2007). The importance of perceived enjoyment has been emphasized by van der Heijden (2004), who claimed that perceived enjoyment dominated perceived usefulness in influencing the adoption behavior of hedonic information systems.…”
Section: Tam Variables As Predictors Of Attitudes Toward Mobile Commumentioning
confidence: 99%